College Algebra: Past, Present, and Future. Issue 7 (9th August 2018) - Tunstall, Samuel Luke
Abstract: Issues within college algebra are well-documented. Over the past two decades, reform has brought about significant modifications in the course, yet to date there has been no synthesis of the efficacy of these efforts. This paper situates college algebra within a historical context, and synthesizes research on reform. I argue that, notwithstanding the successes brought about by change, the course is still not in a position to fulfill quantitative literacy requirements; that is, there exists nontrivial components of quantitative literacy that a college algebra course, by its nature, tends not to provide. I conclude with realistic steps forward for administrators and instructors.